Anterior cruciate ligament injuries in elite badminton athletes: 84% Return to sport, half return to performance - Tan, Y.; Kaldau, N. C.; Lumban-Gaol, I.; Budhiparama, N. C.; Peers, K. (Knee surgery, Sports Traumatology. Arthroscopy, 2024)
Abstract Purpose: Badminton requires fast and pivoting movements, putting athletes at risk of sustaining an anterior cruciate ligament (ACL) injury. The primary purpose is to investigate the return to sport (RTS) and the return to performance (RTP) after an ACL injury in elite badminton athletes. The secondary purpose is to describe ACL injury mechanisms in elite badminton players. Methods: Athletes within the top 200 of the Badminton World Federation World Ranking who sustained an ACL injury between January 2001 and December 2021 were retrospectively included. An anonymous online survey was created in eight languages. RTS, RTP and contributing factors were analysed among athletes aiming to RTP. The injury mechanism was analysed in all participants. Results: Sixty-six athletes from 32 countries were included. Fifty-seven athletes (86.4%) aimed to RTP. Forty-eight out of 57 (84.2%) did RTS. Twenty-nine (50.9%) managed to successfully RTP. Forty-nine (74.2%) of ACL injuries occurred during a competition, 14 (21.2%) occured during training. Thirty-one (49.2%) occurred in the rear court backhand side and 47 (74.6%) occurred during landing after a jump. Conclusion: Forty-eight out of 57 (84.2%) athletes managed to RTS. Half of the athletes managed to successfully RTP. Most of the ACL injuries occurred during competition, in the rear court backhand side and during landing after a jump.